Technology of composting using Tondano lake’s water hyacinth - Friyani David Worotitjan; Sandra E. Pakasi; Wiesje J. N. Kumolontang (Sam Ratulangi University, 2022)
Composting Technology Made from Water Hyacinth (Eichhornia Crassispes) Tondano lake. Friyani David Worotitjan, NIM 14031108032. Supervisor: Dr. Ir. Sandra E. Pakasi, MSi. Dan Wiesje J. N. Kumolontang, SP., MP.This study aims to obtain composting technology made from water hyacinth (Eichhornia Crassispes) in Tondano lake and determine the nutrient content of compost made from water hyacinth (Eichhornia Crassispes) Tondano lake. The method used in this research is the descriptive qualitative method. Sources of data come from primary data and secondary data. With the anaerobic method of composting technology.The results of the study can be concluded that the anaerobic method of composting technology made from water hyacinth (Eichhornia Crassispes) with an EM4 activator has a composting success rate of 85%. And the nutrient content with anaerobic composting technology made from water hyacinth (Eichhornia Crassispes) in this compost is in accordance with the quality requirements of organic fertilizers by the Regulation of the Minister of Agriculture and SNI.Keywords: Technology, Composting, Water HyacinthÂ AbstrakPenelitian ini bertujuan untuk mendapatkan teknologi pengomposan berbahan baku eceng gondok (Eichhornia Crassispes) danau Tondano dan Mengetahui kandungan unsur hara kompos berbahan baku eceng gondok (Eichhornia Crassispes) danau Tondano. Metode yang digunakan dalam penelitian ini adalah metode kualitatif deskriptif. Sumber data berasal dari data primer dan data sekunder. Dengan teknologi pengomposan metode anaerob.Hasil penelitian dapat disimpulkan bahwa Teknologi pengomposan metode anaerob berbahan baku eceng gondok (Eichhornia Crassispes) dengan aktivator EM4 memiliki tingkat keberhasilan pengomposan 85%. Serta kandungan hara dengan teknologi pengomposan anaerob berbahan baku eceng gondok (Eichhornia Crassispes) dalam kompos ini sesuai dengan syarat mutu pupuk organik oleh Peraturan Menteri Pertanian dan SNI. Kata Kunci: Teknologi, Pengomposan, Eceng Gondok.